Being grateful for being: Being, reverence and finitude - Young, Damon A. (Sophia, 2005)
Atheists are rarely associated with holiness, yet they can have deeply spiritual experiences. Once such experience of the author exemplified ‘the holy’ as defined by Otto. However, the subjectivism of Otto’s Kantianism undermines Otto’s otherwise fruitful approach. While the work of Hegel overcomes this, it is too rationalistic to account for mortal life. Seeking to avoid these shortcomings, this paper places ‘holiness’ within a self-differentiating ontological unity, the Heideggerian ‘fourfold’. This unity can only be experienced by confronting groundless finite mortality, and the resulting existential disposition is characterized as ‘reverence’. Reverence is gratitude for mortal existence, and existence itself. Moreover, it is as much political as it is ontological, atheistic as it is theistic.